Nekrolog. Leif Grane in memoriam - True, Henrik (Grundtvig-Studier, 2001)
In Memory of Leif Grane By Henrik True In his commemorative words Henrik True emphasizes Grane’s extensive command of his subject area. Certainly, the interpretation of Martin Luther’s theology was at the heart of his studies, and Grane’s publications about Luther constitute a life’s work in themselves. But beyond the work with the Reformer Grane produced works that will undoubtedly prove to be of lasting importance, too. This will be true, for example, about a number of books and articles about other periods in church history, in fact, there are few centuries in the history of Christianity to which Grane has not devoted an analysis. But it should not be forgotten that beyond his professional activity Grane was also a participant in the general debate on church matters as well as the cultural life of the people, and that he was also a priest. Precisely in considering these aspects of Grane’s life and work, one will find a considerable part of the explanation why it was so important for him to reflect deeply on the relationship between Luther and Grundtvig. That relationship was indeed a difficult one, which would turn out, if taken seriously in its complexity, to provide crucial insights to an understanding of the works of both writers. What is the issue here, is the very core of Luther’s reformatory thinking, scripturalism and its connection with the understanding of the content of the Gospel and the nature of the church service. These connections were of course of crucial importance to professional theology as well as to church life, and to Grane it was evident that this was a field which must not at any price be trivialized by offering simple solutions. Grundtvig’s .church view. must needs be maintained as a significant renewal of the Lutheran tradition, thus proving to be an indispensable intermediate link to a fruitful continuation of Lutheran theology and church life, also in a modem perspective.